Pandemic and education: in search of viable-unedited (Olhar de Professor, 2021)
The present essay aims to promote reflections on the pandemic as a limit situation in the current times, to denounce some of the ideological constraints that obscure the understanding of reality and to point out possibilities in the area of ​​education as a confrontation of what is set. We rely on a critical theoretical framework, with Álvaro Vieira Pinto, Lucien Goldmann, Paulo Freire, Achile Mbembe and Ailton Krenak as main contributions. We are guided by some questions: What does the pandemic unmask? What are the reasons for its denial by a good portion of the population? How can schools act to expose the present epochal unit and announce other ways of seeing and living the world in the near future? We start from the principle that the possible conscience is built within an ideology and that unveiling the fallacies of the necropolitics and the dictates of neoliberalism can point out directions for the construction of viable unedited at school and outside it.
Keywords: Education. Pandemic. Maximum conscience possible. Viable-unedited.